2018
DOI: 10.3346/jkms.2018.33.e177
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Ligation-dependent Probe Amplification Analysis Subsequent to Direct DNA Full Sequencing for IdentifyingATP7BMutations and Phenotype Correlations in Children with Wilson Disease

Abstract: BackgroundMutations in ATP7B cause Wilson disease (WD). However, direct DNA full sequencing cannot detect all mutations in patients with WD. Multiplex ligation-dependent probe amplification (MLPA) analysis is reportedly useful in increasing the diagnostic yield in other genetic disorders with large deletions or insertions. The aim of this study was to evaluate whether the detection rate of ATP7B mutations can be increased by using MLPA.MethodsWe enrolled 114 children with WD from 104 unrelated families based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Our results suggest that large deletions and duplications in the ATP7B gene may be relatively uncommon. This is in concordance with a smaller study from Korea that showed no deletions or duplications detected by MLPA in the ATP7B gene in 24 children with one or no pathogenic variants detected by sequencing 14…”
Section: Wilson Diseasesupporting
confidence: 92%
“…Our results suggest that large deletions and duplications in the ATP7B gene may be relatively uncommon. This is in concordance with a smaller study from Korea that showed no deletions or duplications detected by MLPA in the ATP7B gene in 24 children with one or no pathogenic variants detected by sequencing 14…”
Section: Wilson Diseasesupporting
confidence: 92%
“…Under normal conditions, the Ptype ATPase is responsible for transport of copper from liver to bile (49, 50). It should be written that various mutations occur in the patients suffering from Wilson disease so different patients can have different mutation resulting in P-type ATPase impairment (51,52). Regardless of mutation type in the ATP7B gene, the impaired P-type ATPase leads to copper accumulation in multiple organs with fatal consequences if untreated (53).…”
Section: Wilson and Menkes Disease As Genetically Determined Disordermentioning
confidence: 99%